The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1371/journal.pone.0011134
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Wnt/β-Catenin Signaling Is Required for Cardiac Differentiation in Human Embryonic Stem Cells

Abstract: BackgroundWnt/β-catenin signaling is an important regulator of differentiation and morphogenesis that can also control stem cell fates. Our group has developed an efficient protocol to generate cardiomyocytes from human embryonic stem (ES) cells via induction with activin A and BMP4.Methodology/Principal FindingsWe tested the hypothesis that Wnt/β-catenin signals control both early mesoderm induction and later cardiac differentiation in this system. Addition of exogenous Wnt3a at the time of induction enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
226
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(236 citation statements)
references
References 23 publications
(35 reference statements)
6
226
0
2
Order By: Relevance
“…But, after the mesoderm formation, Wnt signaling prevents differentiation of committed cells into cardiomyocytes [53,56]. Similar time-dependent biphasic effects of Wnt signaling on cardiomyogenesis are also noted in human ES cells [57]. Given the importance of Wnt// β-catenin signaling in cardiomyogenesis, it is not surprising then that selective modulators of this pathway have a strong impact on in vitro cardiomyogenesis.…”
Section: Small Molecules For Directing Stem Cell Differentiation Tmentioning
confidence: 76%
“…But, after the mesoderm formation, Wnt signaling prevents differentiation of committed cells into cardiomyocytes [53,56]. Similar time-dependent biphasic effects of Wnt signaling on cardiomyogenesis are also noted in human ES cells [57]. Given the importance of Wnt// β-catenin signaling in cardiomyogenesis, it is not surprising then that selective modulators of this pathway have a strong impact on in vitro cardiomyogenesis.…”
Section: Small Molecules For Directing Stem Cell Differentiation Tmentioning
confidence: 76%
“…The Activin/BMP4 protocol usually results in > 30 % of beating cardiomyocytes within 2 weeks [14]. Some researchers, however, have reported significant variance in the yields obtained with cell lines and poor reproducibility of different experiments with the same cell line [14,68,121].…”
Section: Induction Of Differentiation By Supplementation With Activinmentioning
confidence: 99%
“…The canonical Wnt pathway is also involved at the first stage of cardiac induction. b-catenin was showed to induce EMT in ESCs and expression of mesodermal markers [221,265,266].…”
Section: Signaling Pathways Underlying Cardiac Differentiationmentioning
confidence: 99%
“…Electrophysiological studies revealed that iPSC-CM display heterogeneous culture including atrial-, nodal-, and ventricular-like action potential (AP) [299,300] that also show variable AP characteristics between studies and within studies with different cell lines [214], differentiation methods [266], and time in culture [301].…”
Section: Characterization Of Ipscs Derived Cardiomyocytesmentioning
confidence: 99%